The Endangered and Protected Carabus hungaricus Fabricius, 1792 (Coleoptera: Carabidae) in Bulgaria: Distributional Patterns and Conservation Status - Teodora M. Teofilova; Nikolay D. Kodzhabashev (Conservation, 2025)
Carabus hungaricus Fabricius, 1792, is a protected Natura 2000 species included in Berne Convention and CORINE. In Bulgaria, it is listed in the Biological Diversity Act and Bulgarian Red Data Book. It is included in the standard form of only one protected area (BG0000322 “Dragoman”) with an ‘unfavourable’ status. This study shows a part of the results from the development of an Action Plan for the protection of Carabus hungaricus in Bulgaria. Data were obtained between 24 May 2021 and 10 December 2023 with the help of 252 pitfall traps from 42 plots. Carabus hungaricus was established in only seven of the sampling sites, with a total of 198 specimens. In those sites, we found 56 other carabid species belonging to 18 zoogeographical categories. The European–Asiatic steppe complex prevailed (30%). The European–Neareastern (17.5%), Palaearctic and European–Central Asian (10.5% each) zoogeographical elements were the most represented. The known range of the species in Bulgaria is limited to the karst steppes of the small mountains around the Sofia Basin. We add four new localities to the distributional map of C. hungaricus and update its altitudinal limit, elevating it to 1200 m. The species is highly vulnerable, strongly attached to the steppe biome and is stenotopic in relation to environmental conditions, thus requiring full conservation of its habitats.